Electrospun Hollow Nanofiber Surfaces as Dielectric Mediums for Highly Sensitive Flexible Capacitive Pressure Sensors in Low pressure Regimes - Siddique, Shaharyar (My University, 2025)
Flexible capacitive pressure sensors have gained importance in the electronics industry with varying structural designs for monitoring, soft robotics and sensing needs. However, achieving high sensitivity at low-pressures with soft, flexible, and scalable dielectric materials remains a key challenge. It requires dielectric layers that are both soft and low permittivity to achieve high sensitivity. This thesis addresses this challenge by developing a flexible capacitive pressure sensor that employs coaxially electrospun hollow polycaprolactone (PCL) nanofibers as a compressible dielectric spacer. The process produces continuous core–shell fibers with a removable inner core, yielding thin-walled hollow fibers with enhanced air-gap volume. Compared to conventional solid nanofiber dielectrics, the hollow fiber dielectric exhibits significantly higher sensitivity in the low-pressure regime due to increased compressibility and a lower effective permittivity. The sensor achieved a maximum sensitivity of approximately 1.05 kPa-1 at low-pressure, while also demonstrating good cyclic stability and a fast response. These results indicate that the coaxial electrospinning approach is highly scalable, and integration with 3D printing as well as dielectric property enhancements are proposed to further advance its performance.
Keywords: Keywords: Capacitive Pressure Sensors, Coaxial Electrospinning, Polycaprolactone PCL, Dielectric, Sensitivity.